2021
DOI: 10.1016/j.jbc.2021.100964
|View full text |Cite
|
Sign up to set email alerts
|

Purification of active human vacuolar H+-ATPase in native lipid-containing nanodiscs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Recently, a study showed that intact active V-ATPase could be purified from a HEK293 cell line that stably expressed subunit a4 23 . We took advantage of this remarkable work to seek for modulators under different cell culture conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a study showed that intact active V-ATPase could be purified from a HEK293 cell line that stably expressed subunit a4 23 . We took advantage of this remarkable work to seek for modulators under different cell culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The V-ATPase was purified with the nanodiscs scaffold protein MSP1E3D1 and reconstituted into native lipid-containing nanodiscs according to an established protocol (Supplementary Fig. 1a ) 23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation